Role of PLCγ1 in the modulation of cell migration and cell invasion in glioblastoma. (January 2022) - Marvi, Maria Vittoria; Mongiorgi, Sara; Ramazzotti, Giulia; Follo, Matilde Y.; Billi, Anna Maria; Zoli, Matteo; Mazzatenta, Diego; Morandi, Luca; Asioli, Sofia; Papa, Veronica; McCubrey, James A.; Suh, Pann-Ghill; et al.
Abstract: Phosphoinositide-specific phospholipases C (PLCs) are a class of enzymes involved in several cell activities, such as cell cycle regulation, proliferation, differentiation and cytoskeletal dynamics. Among these enzymes, PLCγ1 is one of the most expressed PLCs in the brain, contributing to a complex network in the developing nervous system. Several studies have shown that PLCγ1 signaling imbalance is linked to several brain disorders, including glioblastoma, the most aggressive brain tumor in adults. Indeed, it has been demonstrated a link between PLCγ1 inhibition and the arrest of glioma cell motility of fetal rat brain aggregates and the impairment of cell invasion abilities following its down-regulation. This study aims to determine the pathological influence of PLCγ1 in glioblastoma, through a translational study which combines in silico data, data from glioblastoma patients' samples and data on engineered cell lines. We found out that PLCγ1 gene expression correlates with the pathological grade of gliomas, and it is higher in fifty patients' glioblastoma tissue samples compared to twenty healthy controls. Moreover, it was demonstrated that PLCγ1 silencing in U87-MG leads to a reduction in cell migration and invasion abilities. The opposite trend was observed following PLCγ1 overexpression, suggesting an interesting possible involvement of PLCγ1 in gliomas' aggressiveness.